CCAFS Climate Change and Social Learning: Phase 2 concept note - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The aim of the CCAFS Climate Change and Social Learning (CCSL) Initiative is to better understand and tap the potential of social learning for research on climate change, agriculture and food security. In June 2013, the CCSL “Plan-and- Writeshop” reviewed the prior 18 months of activities and products. Ideas and a vision for the next phase of work were then set out. This concept note outlines these ideas and the vision for Phase 2 of the CCSL Initiative in greater depth. First, the definition and utility of CCSL are revisited. Next, the CCSL Strategy set out at the end of Phase 1 is summarised. The vision for Phase 2 as well as the hypotheses behind it are then explained.